Proanthocyanidins and Where to Find Them: A Meta-Analytic Approach to Investigate Their Chemistry, Biosynthesis, Distribution, and Effect on Human Health - Giuseppe Mannino; Giorgia Chinigò; Graziella Serio; Tullio Genova; Carla Gentile; Luca Munaron; Cinzia Margherita Bertea (MDPI AG, 2021)
Proanthocyanidins (PACs) are a class of polyphenolic compounds that are attracting considerable interest in the nutraceutical field due to their potential health benefits. However, knowledge about the chemistry, biosynthesis, and distribution of PACs is limited. This review summarizes the main chemical characteristics and biosynthetic pathways and the main analytical methods aimed at their identification and quantification in raw plant matrices. Furthermore, meta-analytic approaches were used to identify the main plant sources in which PACs were contained and to investigate their potential effect on human health. In particular, a cluster analysis identified PACs in 35 different plant families and 60 different plant parts normally consumed in the human diet. On the other hand, a literature search, coupled with forest plot analyses, highlighted how PACs can be actively involved in both local and systemic effects. Finally, the potential mechanisms of action through which PACs may impact human health were investigated, focusing on their systemic hypoglycemic and lipid-lowering effects and their local anti-inflammatory actions on the intestinal epithelium. Overall, this review may be considered a complete report in which chemical, biosynthetic, ecological, and pharmacological aspects of PACs are discussed.